The inactivation of the Niemann Pick C1 cholesterol transporter restricts SARS-CoV-2 entry into host cells by decreasing ACE2 abundance at the plasma membrane - Piergiorgio La Rosa; Jessica Tiberi; Enrico Palermo; Roberta Stefanelli; Sofia Maria Luigia Tiano; Sonia Canterini; Mirko Cortese; John Hiscott; Maria Teresa Fiorenza (Cell & Bioscience)
Abstract Background The Niemann Pick C1 (NPC1) protein is an intracellular cholesterol transporter located in the late endosome/lysosome (LE/Ly) that is involved in the mobilization of endocytosed cholesterol. Loss-of-function mutations in the NPC1 gene lead to the accumulation of cholesterol and sphingolipids in LE/Ly, resulting in severe fatal NPC1 disease. Cellular alterations associated with NPC1 inactivation affect both the integrity of lipid rafts and the endocytic pathway. Because the angiotensin-converting enzyme 2 (ACE2) and type 2 serine transmembrane protease (TMPRSS2), interactors of the SARS-CoV-2 Spike protein also localize to lipid rafts, we sought to investigate the hypothesis that NPC1 inactivation would generate an intrinsically unfavorable barrier to SARS-CoV-2 entry. Results In this study, we show that inhibition of the cholesterol transporter activity of NPC1 in cells that express both ACE2 and TMPRSS2, considerably reduces SARS-CoV-2 infectivity, evaluated as early as 4 h post-infection. Mechanistically, treatment with NPC1 specific inhibitor U18666A relocalizes ACE2 from the plasma membrane to the autophagosomal/lysosomal compartment, thereby reducing SARS-CoV-2 entry into treated cells. Reduction of viral entry was observed for both fully infectious SARS-CoV-2 virus and with a pseudotyped VSV-Spike-GFP virus. For instance, U18666A-treated Caco-2 cells infected with the pseudotyped VSV-Spike-GFP showed a > threefold and > 40-fold reduction in virus titer when infectivity was measured at 4 h or 24 h post-infection, respectively. A similar effect was observed in CRISP/R-Cas9-edited Caco-2 cells, which were even more resistant to SARS-CoV-2 infection as indicated by a 97% reduction of viral titers. Conclusion Overall, this study provides compelling evidence that the inhibition of NPC1 cholesterol transporter activity generates a cellular environment that hinders SARS-CoV-2 entry. ACE2 depletion from the plasma membrane appears to play a major role as limiting factor for viral entry.